On the Integration of a Nonlinear System of Differential Equations - Oleinik, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study a system of nonlinear differential equations used as basic for the construction of triangular models for commutative systems of linear nonself-adjoint bounded operators.